Characterisation of the activation and reaction behaviour and determination of the emissivity of reactive nickel-aluminium particles with regenerated fibre Bragg gratings. (February 2019) - Grohmann, S; Lindner, M; Langhans, G; Roths, J; Zaeh, M F
Abstract: Reactive particles represent a customisable heat source for joining applications as each reactive particle is able to undergo an exothermic, self-sustaining reaction. Microwaves are used to homogeneously initiate this reaction and allow the resulting temperature-time profiles to be influenced. The possibility to derive cause-effect relationships between the different particle structures, the activation energy, and the resulting maximum temperatures is essential for developing a resource-efficient, tailored heat source in production engineering. The reaction of reactive nickel and aluminium particles generates heat and thus temperatures up to 1500 K within milliseconds. A promising temperature measurement method despite an unknown emissivity are optical fibre sensors. These feature high frame rates, a compact design, and resistance to high temperatures as well as to electromagnetic waves. In this paper, the investigation of the use of regenerated fibre Bragg gratings (RFBG) as a new, innovative approach to characterise reactive particles is described. Experimental studies with an infrared camera and RFBG demonstrated that RFBG retain their functionality while being exposed to microwaves and high temperatures. The good accordance of the recorded RFBG-based temperature evolutions with infrared thermography data confirmed the suitability of RFBG as a sophisticated characterisation method and for determining the emissivity of reactive metal particles.